PATIENT SATISFACTION WITH TELECONSULTATION DURING COVID-19 PANDEMIC: A DESCRIPTIVE STUDY FOR MENTAL HEALTH CARE IN MALAYSIA - Othman, Elza; Giampietro, Vincent; Mohamad, Mahadzirah (Malaysian Journal of Public Health Medicine, 2021)
The recent novel coronavirus disease 2019 (COVID-19) outbreak has led health care providers to shift rapidly from on-site consultation towards teleconsultation. However, knowledge about patient satisfaction with teleconsultation, particularly for mental health care, is limited and demands further investigation. This study aimed to evaluate patient satisfaction with teleconsultation in mental health care during the COVID-19 pandemic. The study also aimed to identify the leading contributing factors to patient satisfaction with teleconsultation. A convenience sampling method was employed. An online survey was conducted between June 8 and August 3, 2020. A 14-item questionnaire was used to assess the patient's level of satisfaction in four domains of satisfaction. A total of 106 questionnaires were received. Respondents reported a high level of satisfaction with teleconsultation. The convenience of not having to travel to the health center for consultation was the leading contributing factor to patient satisfaction with teleconsultation. However, patients reported that they were least satisfied with teleconsultation because they could not express their feelings deeply to the provider. The current study provides preliminary evidence that teleconsultation may be a satisfactory mode of communication during the COVID-19 pandemic for mental health care in Malaysia. Most importantly, consultation in mental health care should carry on to be performed remotely to prevent the spread of infectious disease. Future research is warranted to provide a better understanding of other factors contributing to patient satisfaction with teleconsultation and ways to improve them.